Weight- perception in male career firefighters and its association with cardiovascular risk factors - Baur, Dorothee M (BioMed Central, 2012)
BACKGROUND: The prevalence of obesity has reached epidemic proportions worldwide, and is also increasing among public safety professionals like firefighters who are expected to be fit and more active. The present study evaluates the associations among Body Mass Index (BMI), weight perception and cardiovascular risk factors in 768 male career firefighters from two Midwestern states in the United States. METHODS: A physical examination was performed and fasting blood samples were taken. Cardio-respiratory fitness (CRF) was determined from symptom- limited maximal treadmill exercise testing with electrocardiogram (ECG) monitoring and estimation of oxygen consumption (metabolic equivalents, METS) using the Bruce protocol. A health and lifestyle questionnaire was administered with standardized written instructions for completion. Self-reports of weight perception were extracted from responses to the completed multiple choice questionnaire. Baseline characteristics were described using the mean (standard deviation) for continuous variables and frequency for categorical variables. Group comparisons were calculated using analysis of variance (ANOVA). Linear models and logistic regression models were used to adjust for possible confounders. Logistic regression analyses were used to calculate the odds ratios of underestimating one’s weight category. RESULTS: A high proportion of overweight and obese male career firefighters underestimate their weight categories (68%). The risk of underestimating one’s weight category increased by 24% with each additional unit of increasing BMI after adjustment for age and CRF. When divided into six groups based on combinations of measured BMI category and weight perception, there were significant differences among the groups for most cardiovascular risk factors. After adjustment for age and BMI, these differences remained statistically significant for CRF, amount of weekly exercise, prevalence of Metabolic Syndrome (MetSyn), body fat percentage and cholesterol measurements. CONCLUSION: A high proportion of overweight and obese male career firefighters underestimate their measured BMI categories. As a result, they are unlikely to fully appreciate the negative health consequences of their excess weight. The results of this study emphasize the importance of objectively measuring BMI and then informing patients of their actual weight status and the associated disease risks.